Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Pekerja Pada Perusahaan Penyosohan Beras di Desa Jagapati, Angantaka, Sedang kec. Abiansemal kab. Badung - Dwipayana, Krisna; Sucipta, I Nyoman; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 8 No 1 (2020): April, 2019)
This study aims to determine the effect of occupational safety and health (K3) on worker performance and to find out the factors that most influence the performance of workers in the rice fueling company. The questionnaire was used as a data collection tool that was disseminated to 20 employees in the suppression of rice in the area of ??Sedang, Angataka, jagapati, Kec.Abiansemal, Kab. Kadung. Analysis of this study were emalyzed using validity test, normality test, reliability test and linear regression test. The results of the validity test analysis are 9 invalid questions. The results of the normality test, the data are normally distributed with a significance value of 0.819. The reliability test obtained the results of the data that was reliable with the value of Cronbach's Alpha 0.933. As well as the analysis of the linear regression test the results are closely related. From the research conducted it can be concluded that (1) the relationship of Occupational Safety and Health (K3) to the workforce can be seen from the magnitude of the coefficient of determination (R2) the relationship between the factors that influence K3 and the performance of workers. The performance of workers with supervisory factors has a coefficient of determination of 61.27% and with occupational safety of 88.51%, with health of workers of 86.09%, (2) Factors that most influence the performance of workers in the company of raising rice are factors of work safety, where the closeness of the relationship between the two is 61.27%.